Broken smiles: The impact of untreated dental caries and missing anterior teeth on employment. (16th April 2019) - Halasa‐Rappel, Yara A.; Tschampl, Cynthia A.; Foley, Mary; Dellapenna, Martha; Shepard, Donald S.
Abstract: Objectives: We aimed to quantify the impact of dental caries and missing anterior teeth on employment, estimate the impact of a routine dental visit on the health of anterior teeth, and the benefits of expanding dental coverage for nonelderly adults. Methods: We used the 2013–2014 Continuous National Health and Nutritional Examination Survey to develop a dental problem index (DPI) using tooth counts and tooth surface conditions. We estimated the impact of DPI on employment with logistic regression, controlling for seven demographic and socioeconomic covariates. We used a routine dental visit within 6 months as a proxy for access to dental services, and a linear regression to predict the DPI score for an average individual with and without a recent routine dental visit. We then computed the incremental probability of employment associated with a recent routine dental visit. Finally, we estimated the additional number of working age adults who might become employed due to improved access to dental services. Results: The probability of being employed was negatively associated with poor oral health: a one‐point increase in DPI decreased the odds of being employed by 7.70 percent (CI: 5.15–10.19%). Having a routine dental visit had a negative and statistically significant impact on DPI [−0.41 (CI: −0.68 to −0.14)]. The incremental probability of employment associated with a routine dental visit was 0.62 percent (CI: 0.21–1.03%). Conclusions: Oral health in the United States is worse among minorities and poor than among other residents. The benefits associated with access to dental care should justify expanding dental services.